Peran Organisasi Ikatan Mahasiswa Kepulauan Riau di Kota Medan dalam Menumbuhkan Karakter Peduli Sosial - Gracia Veronica Siregar; Liber Siagian (Journal on Education, 2024)
This study aims to find out how the Role of the Riau Islands Student Association Organization in Medan City in Fostering Social Care Character based on role theory, external organization, social care character (empathy, awareness) and social interaction. The method used in this study is a descriptive qualitative research method. The data collection instruments used in this study are by conducting observations, conducting interviews and documentation. The research subjects consisted of 5 daily management bodies, 5 commissioners and 5 members of the Riau Islands Student Association organization in Medan City. The data analysis techniques used in this study are data reduction, data presentation and conclusion drawn. The results of the study show that IMKR-Medan plays a role in the development of all potentials in students, such as guiding, shaping, sharpening, and instilling character values, one of which is the character value of social care to be encouraged in IMKR-Medan, The process of designing work programs itself can be realized by IMKR-Medan with every activity that can implement empathy, social awareness through social interaction so that the organization can grow the character of social care. However, to carry out these work programs is not as easy as imagined because there are various obstacles and obstacles faced in making students aware of the importance of fostering social care characters such as fund problems, Difficulties in accessing transportation and very difficult locations for students who are far from the secretariat, clashes in student activities and lack of communication. Thus, the IMKR-Medan organization has a role in fostering the character of social care to members through activities that have been designed in these work programs. Keywords: Role of External Organizations, Social Care Character, IMKR-Medan